Propafenone and propranolol dual toxicity - Moonis Farooq; Faisal Qureshi; Wael Kamkoum; Feras Abuzeyad (Journal of the American College of Emergency Physicians Open)
Abstract Propranolol is a highly lipid‐soluble beta‐receptor antagonist and propafenone is a potent class 1c anti‐arrhythmic agent with strong Na‐channel blockade effect. We describe a novel case of dual overdose of propafenone and propranolol resulting in hypotension, generalized seizures, and reduced level of consciousness that was successfully treated. A 52‐year‐old female ingested 500 mg of propranolol and 1.5 g of propafenone. The patient was brought to the emergency department (ED) and exhibited signs of systemic toxicity and reduced level of consciousness. The patient was treated as a case of combined β‐blocker and propafenone toxicity using high dose insulin, NaHCO3, glucagon, atropine, and dopamine. She started improving and becoming more alert, with subsequent ECGs revealing normal sinus rhythm. The patient was discharged 4 days later. We believe that early administration of NaHCO3 should be administered in patients exhibiting signs of Na‐channel blockade.